2018
DOI: 10.1093/mnras/sty2734
|View full text |Cite
|
Sign up to set email alerts
|

SOFIA mid-infrared observations of Supernova 1987A in 2016 – forward shocks and possible dust re-formation in the post-shocked region

Abstract: The equatorial ring of Supernova (SN) 1987A has been exposed to forward shocks from the SN blast wave, and it has been suggested that these forward shocks have been causing on-going destruction of dust in the ring. We obtained SOFIA FORCAST 11.1, 19.7 and 31.5 µm photometry of SN 1987A in 2016. Compared with Spitzer measurements 10 years earlier, the 31.5 µm flux has significantly increased. The excess at 31.5 µm appears to be related to the Herschel 70 µm excess, which was detected 5 years earlier. The dust m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 69 publications
4
46
0
Order By: Relevance
“…A large amount of dust (0.1−0.5 M ) is formed in situ in SN remnants (Matsuura et al 2011), but it is still unclear how much dust is destroyed by the reverse shock or reformed. Matsuura et al (2019) interpreted the increase in the 31.5 µm photometry in SN1987A obtained from SOFIA FORCAST 11.1, 19.7 in 2016 with respect to 10 years earlier as a possible indication of dust re-condensation in the forward shock. Indeed, the mass of dust needed to explain the emission of this dust component at a temperature of ∼85 K is more than ten times larger than that estimated 10 years earlier.…”
Section: Notesmentioning
confidence: 92%
See 1 more Smart Citation
“…A large amount of dust (0.1−0.5 M ) is formed in situ in SN remnants (Matsuura et al 2011), but it is still unclear how much dust is destroyed by the reverse shock or reformed. Matsuura et al (2019) interpreted the increase in the 31.5 µm photometry in SN1987A obtained from SOFIA FORCAST 11.1, 19.7 in 2016 with respect to 10 years earlier as a possible indication of dust re-condensation in the forward shock. Indeed, the mass of dust needed to explain the emission of this dust component at a temperature of ∼85 K is more than ten times larger than that estimated 10 years earlier.…”
Section: Notesmentioning
confidence: 92%
“…On the other hand, for SNe II, Gall et al (2014) found evidence for the presence of 0.1-0.5 M of large grains in SN2010jl and thus able to survive the passage of the reverse shock. In addition, recent observations from Matsuura et al (2019) of SN1987 show that dust might re-condense in the cooling gas that experienced the passage of the forward shock. In the former case, this might indicate that dust can be efficiently reformed after being destroyed by shocks.…”
Section: Introductionmentioning
confidence: 99%
“…An easy comparison between these various models is hampered by the different assumptions made to describe the ambient densities, the density contrast between dust clumps and the surrounding medium, the grain size distribution and the composition of supernova dust species. In addition, our inferred dust survival rate will account for the fact that some supernova remnants will not experience a reverse shock (e.g., the Crab Nebula) due to the low density of the surrounding medium, and should thus be considered as an "effective" dust survival rate as it is convoluted with the probability that a reverse shock will be generated through the interaction with a dense circum-or interstellar medium, and that dust might be able to reform after the shock passage (e.g., Matsuura et al 2019). Current observational studies tend to be biased towards interacting supernova remnants or pulsar wind nebulae which provide a heating mechanism through shock interaction or through the presence of a pulsar, respectively.…”
Section: Net Supernova Dust Production Ratesmentioning
confidence: 99%
“…On planet Earth, through hydrogen bonding between water monomers, stable water nanoclusters, both neutral and ionized, are easily formed in molecular beams (Carlon, 1981), occur naturally in the water vapour of earth's atmosphere (Aplin and McPheat, 2005), and are produced from amorphous ice by energetic ion bombardment (Martinez, 2019). In the cosmos, therefore, a natural route to water nanocluster formation would be via the ejection from amorphous water-ice coatings of cosmic dust grains (Dulieu et al ., 2010; Potapov et al ., 2020), which are believed to be abundant in interstellar clouds because they are a product of supernovae explosions (Matsuura et al ., 2019). As a prime example, cosmic ray ionization of H 2 molecules adsorbed on amorphous ice-coated dust grains can lead to the reaction (Duley, 1996): …”
Section: Water Nanoclustersmentioning
confidence: 99%
“…However, quantum field theory predicts a vacuum energy density that is too large by up to a factor of 10 120 (Zeldovich and Krasinski, 1968; Weinberg, 1989), which is the well-known cosmological constant problem. I propose that nanoclusters of water molecules ejected by cosmic rays from amorphous ice layers on ubiquitous cosmic dust produced from exploding supernovae (Matsuura et al ., 2019), albeit at low density compared to elemental hydrogen and oxygen, excited to their diffuse Rydberg states (Herzberg, 1987), are possible candidates for baryonic dark matter. The cut-off terahertz (THz) vibrational frequencies of such water nanoclusters are close to the ν c ≅ 1.7 THz cut-off frequency of zero-point-energy vacuum fluctuations proposed to account for the small value of vacuum energy and cosmological constant (Beck and Mackey, 2005, 2007).…”
Section: Introductionmentioning
confidence: 99%